Pengaruh Pemasangan Kapasitor terhadap Cop (Coefficient Of Performance) Air Conditioning - Anwar Syahputra, Syofyan; Mustakim, Mustakim (P3M Politeknik Negeri Indramayu, 2016)
Non linear load harmonics cause, Air Conditioning is one of the main types of inverters that generate non linear load harmonics. Harmonics on the Air Conditioning so that the reduction must not interfere with the quality of power on the system and network. The ability of an Air Conditioning unit to cool a room can be known as Coefficient Of Performance (COP). This can be seen from the comparison between the heat energy required to cool the room with the electric energy used on the unit. In this case you will know the impact caused by the reduction of the harmonics of the COP. Reduction of harmonics used in this study using 16 F capacitor which also serves as a power factor improvement. The results obtained after using the capacitor found impairment harmonic currents (IHDi). After the measurement of the COP also increased from 2,740 becomes 3,176. This proves that the capacitor also function besides improving the power factor can reduce the harmonics an improve the COP.